SINTESIS PATI SAGU IKATAN SILANG FOSFAT BERDERAJAT SUBSTITUSI FOSFAT TINGGI DALAM SUASANA ASAM [Synthesis of Cross-Linked Sago Starch Phosphate with the Highest Degree of Substitution of Phosphate Under Acidic Condition] - Jorion Romengga; Tun Tedja Irawadi; Retno Djulaika; . Muntamah; Ahmad Zakaria (Jurnal Teknologi dan Industri Pangan, 2011)
Cross-linked sago starch phosphate (SgP) with high phosphorus contents was successfully synthesized by reacting sago with a mixture of primary and secondary sodium phosphates under acidic condition. The experimental variables investigated include pH, temperature, reaction time, and mixture rate. The physicochemical properties evaluated were moisture, swelling power, water binding capacity, transmittance (%T) and percent amylose (%Am), while the pasting properties examined were pasting time, pasting temperature, viscosity at peak, final, and setback. The granule structure was observed by scanning electron microscope and X-ray diffraction. The results showed that the maximum degree of phosphate substitution was obtained at pH of 6.50, 40°C, 20 minutes of reaction time and 300 rpm of mixing rate. The physicochemical (%T and %Am) and pasting (viscosity at peak, final, and setback) properties of SgP were significantly different (P<0.01) from Sg. Structure of SgP was characterized by FT-IR and the results indicated a new absorption peak at 2362.87 cm-1 which was characterized as the phospho-diester (RO-PO3-R’) stretching vibration. In the fingerprint area, there were two new absorption peaks at 1242.05 and 989.79 cm-1 which were characterized as the P=O and C-O-P vibration, respectively. Sago granules were substantially altered after cross-linking.